Dopamine drives persistent remodelling of the maternal brain - Jennifer C. O’Chan; Giuseppina Di Salvo; Ashley M. Cunningham; Sohini Dutta; Elizabeth Brindley; Benjamin H. Weekley; Winnie Chen; Rasika R. Iyer; Ethan Wan; Cindy Zhang; Naguib Mechawar; Gustavo Turecki; et al. (Nature, 2026)
Abstract Pregnancy and postpartum experiences represent transformative physiological states that impose lasting demands on the maternal body and brain, resulting in lifelong neural adaptations 1–6 . However, the precise molecular mechanisms that drive these persistent alterations remain poorly understood. Here we used brain-wide transcriptomic profiling to define the molecular landscape of neuroplasticity induced by reproductive experience, identifying the dorsal hippocampal formation (dHF) as a key site of transcriptional remodelling. Combining single-cell RNA sequencing with a maternal–pup separation paradigm, we additionally found that chronic postpartum stress significantly disrupts dHF adaptations by altering dopamine dynamics, leading to changes in the dopamine-dependent histone post-translational modification, H3 dopaminylation, which causally mediates downstream alterations in gene expression and behaviour. In human dorsal subiculum, a brain structure within the dHF, we uncovered conserved patterns of parity-dependent alterations in H3 dopaminylation and transcription. We further established the sufficiency of dopamine modulation in regulating these adaptations via chemogenetic suppression of dopamine release into the dHF, which recapitulated key epigenomic and behavioural features of reproductive experience in virgin female mice. In sum, our findings establish dopamine as a central regulator of parity-induced neuroadaptations in humans and mice, revealing a fundamental transcriptional mechanism by which female reproductive experience remodels the brain to sustain long-term behavioural adaptations.